Scalably Nanomanufactured Atomically Thin Materials‐Based Wearable Health Sensors. Issue 1 (23rd November 2021) - Zhang, Ruifang; Jiang, Jing; Wu, Wenzhuo
Abstract : Wearable multimodal sensors could enable the continuous, non‐invasive, precise monitoring of vital human signals critical for remote health monitoring and telemedicine. Atomically thin materials with intriguing physical characteristics, rich chemistry, and extreme sensitivity to external stimuli are attractive for implementing high‐performance wearable sensors. Despite the increased interest and efforts in 2D materials‐based wearable sensors, reducing the manufacturing and integration costs while improving the product performance remains challenging. Previous review articles provided good coverage discussing the material and device aspects of 2D materials‐based wearable devices. However, few reviews discussed the status quo, prospects, and opportunities for the scalable nanomanufacturing of 2D materials wearable sensors for health monitoring. To fill this gap, the recent advances in 2D materials‐based wearable health sensors are reviewed. The structure design, fabrication processing, the mechanisms of 2D materials‐based wearable health sensors, and their applications for human health monitoring are discussed. More significantly, a systematic discussion of the state‐of‐the‐art and technological gaps for enabling future design and nanomanufacturing of 2D materials wearable health sensors are provided. Finally, the challenges and opportunities associated with the scalable nanomanufacturing of 2D wearable health sensors are discussed. Abstract : Herein, the scalable nanomanufacturing of 2D materials‐based wearable sensors for health monitoring, including synthesis, fabrication, devices, and applications, is overviewed.